Does a health crisis change how we value health?. (23rd July 2021) - Webb, Edward J. D.; Kind, Paul; Meads, David; Martin, Adam
Abstract: General population health state values are used in healthcare resource allocation, including health technology assessment. We examine whether UK general population health valuations changed during the COVID‐19 pandemic. Ratings of EQ‐5D‐5L health states 11111 (no problems), 55555 (extreme problems), and dead were collected in a UK general population survey during the pandemic (April–May 2020) using the 0 = worst imaginable health, 100 = best imaginable health visual analog scale (EQ‐VAS). Ratings for 55555 were transformed to a full health = 1, dead = 0 scale. Responses were compared to similar data collected pre‐pandemic (2018). After propensity score matching to minimize sample differences, EQ‐VAS responses were analyzed using Tobit regressions. On the 0–100 scale, 11111 was rated on average 8.67 points lower, 55555 rated 9.56 points higher, and dead rated 7.45 points lower post‐pandemic onset compared to pre‐pandemic. On the full health = 1, dead = 0 scale, 55555 values were 0.09 higher post‐pandemic onset. There was evidence of differential impacts of COVID‐19 by gender, age, and ethnicity, although only age impacted values on the 1–0 scale. COVID‐19 may have affected how people value health. It is unknown whether the effect is large enough to have policy relevance, but caution should be taken in assuming pre‐COVID‐19 values are unchanged.